2022
DOI: 10.3390/s22051764
|View full text |Cite
|
Sign up to set email alerts
|

A Sensor for Characterisation of Liquid Materials with High Permittivity and High Dielectric Loss

Abstract: This paper reports on a sensor based on multi-element complementary split-ring resonator for the measurement of liquid materials. The resonator consists of three split rings for improved measurement sensitivity. A hole is fabricated at the centre of the rings to accommodate a hollow glass tube, through which the liquid sample can be injected. Electromagnetic simulations demonstrate that both the resonant frequency and quality factor of the sensor vary considerably with the dielectric constant and loss tangent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The split-ring resonator calculation is used to predict the geometric structure in the beginning stages of the sensor design by using equations (1)-(3) [25,26]. A microwave microstrip resonator and a planar ring resonator make up the sensor architecture.…”
Section: Figure 2 the Basic Concept Of Geometrymentioning
confidence: 99%
“…The split-ring resonator calculation is used to predict the geometric structure in the beginning stages of the sensor design by using equations (1)-(3) [25,26]. A microwave microstrip resonator and a planar ring resonator make up the sensor architecture.…”
Section: Figure 2 the Basic Concept Of Geometrymentioning
confidence: 99%
“…Numerous microwave sensors have been developed to characterize various materials, including oils [ 5 , 6 , 7 ], coal [ 8 , 9 ], glucose [ 10 , 11 , 12 ], solids [ 13 , 14 , 15 ], gases [ 16 , 17 , 18 ], and gesomin [ 19 ]. In particular, microwave sensors are also widely used for detecting liquid samples (such as ethanol) based on the glass tube method [ 20 , 21 ], LC method [ 22 ], or microfluidic channel method [ 23 , 24 ]. From the results in the literature, it is found that the microfluidic channel method leads to the highest sensitivity of up to 268 MHz/RIU compared to other methods.…”
Section: Introductionmentioning
confidence: 99%
“…The main sensing element of these microwave sensors are resonator-based as it offers several advantages like simple design, high performance characteristics, low cost, and ease of fabrication. For example, the split-ring resonator [ 26 ], complementary split-ring resonators (CSRR) [ 21 ], substrate-integrated waveguide resonator [ 25 ], Minkowski-like fractal resonator [ 31 ], complementary circular spiral resonator [ 28 ], gap waveguide cavity resonator [ 27 ], multiple split-ring resonator [ 33 ] and, multiple complementary split-ring resonator [ 29 ], which are coupled to a transmission line, have gained considerable attention for potential sensing applications with various liquid samples. Microwave sensors based on conventional complementary split-ring resonators have achieved a sensitivity of 268 MHz/RIU [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Complementary SRRs (CSRR) which are the negative image of SRRs, have also been thoroughly investigated 19 22 . Javed et al 19 and then Wang et al 20 followed a similar approach to characterize complex permittivities of water–ethanol solutions. Their designs were based on multiple CSRRs, consisting of a defected ground structure with multiple interconnected rings, which are excited by a microstrip line on the opposite side of the substrate.…”
Section: Introductionmentioning
confidence: 99%